Investigation of Isatis Tinctoria and Isatis Buschiana Stalks as Raw Materials for Pulp and Paper Production - Nazan Comlekcioglu (University of Zagreb, Faculty of Forestry and Wood Technology, 2016)
Isatis tinctoria and Isatis buschiana were evaluated as raw materials for pulp and paper production. Chemical composition and morphological aspects of Isatis stalks were determined. Lignin contents of I. tinctoria and I. buschiana were 23.9 % and 19.9 %, respectively. alfa-cellulose ratio was found to be 48.5 % in I. tinctoria and 32.9 % in I. buschiana. Fiber length, fiber diameter, lumen diameter and cell wall thickness were measured and the obtained data was used to calculate felting rate, elasticity coeffi cient, rigidity coefficient, runkel index and F factor. Handsheets were produced from Isatis stalks, and physical and optical properties were determined. Breaking length, tear index and burst index values were higher for the beaten pulp than for unbeaten pulp, while brightness and whiteness values were higher in unbeaten pulp.